Tribological performance and lubrication mechanism of phosphate nanoflowers as oil-based additives - Linlin Duan; Dan Jia; Shengpeng Zhan; Suling Huang; Yijie Jin; Haitao Duan (Friction)
In this work, as a new type of oil-based additive, a phosphate mixture of (Sr0.9Ca0.1)3(PO4)2 and Sr3(PO4)2 (SrP) with a flower-like structure was synthesized. Compared with pure poly-α-olefin-8 (PAO8), when a titanium alloy is lubricated, the use of 20 wt% SrP for lubrication can reduce the coefficient of friction (COF) by 69.89% and the wear rate (WR) by 99.86%. The extraordinary tribological performance was attributed to the deposition of a layer of SrP on the surface of the titanium alloy. On the one hand, the deposition layer formed by SrP can prevent direct contact between friction pairs, protect the surface of the titanium alloy, and prevent adhesion wear of the titanium alloy. On the other hand, the low-shear interlayer sliding of SrP nanosheets inside the deposition layer was beneficial for friction reduction. X-ray photoelectron spectroscopy (XPS) confirmed that after frictional sliding, the active group phosphate in SrP was activated, and other metals were oxidized to produce a series of oxides. In addition, phosphate can form P‒O‒Ti bonds with titanium at the interface, which is the key to SrP deposition and adsorption on the surface of titanium alloys. The SrP additive not only exhibited excellent performance in lubricating titanium alloy discs but also stainless steel 304, 42CrMo, and tin bronze. After lubrication with 20 wt% SrP additive, the wear tracks of stainless steel 304 and 42CrMo were not detected, and WR of tin bronze decreased by 92%. An interface lubrication mechanism has been proposed that may be beneficial for the design and application of new lubricating materials.